An Analysis of Ambiguity used in Maleficent: Mistress of Evil Movie: Semantic - Nur Fadila Rahmanita; Ervina CM Simatupang (Budapest International Research and Critics University, 2022)
This research aims to determine what type of ambiguity and meaning are found in Maleficent: Mistress of Evil. The study's data was gathered from a 2019 American fantasy film titled Maleficent: Mistress of Evil that was made by Walt Disney Pictures. Film is a form of visual art that uses moving images to simulate experiences or otherwise convey ideas, narratives, perceptions, feelings, beauty, or atmosphere. The study's theoretical framework is based on Stephen Ullmann's (1977) theory. The researcher used a qualitative approach because the data in this study is delivered in the form of words or sentences. The researcher discovered data on homonymy, homograph, homophones, polysemy, and structural ambiguity. Due to a lack of data, the results of this study revealed six data points. The lexical data (66.7%) dominates this analysis out of the six. Following the phonological data (16.7%) and structural data (16.6%).